Cover Picture: Inherently Chiral Macrocyclic Oligothiophenes: Easily Accessible Electrosensitive Cavities with Outstanding Enantioselection Performances (Chem. Eur. J. 47/2014). Issue 47 (17th November 2014) - Sannicolò, Francesco; Mussini, Patrizia R.; Benincori, Tiziana; Cirilli, Roberto; Abbate, Sergio; Arnaboldi, Serena; Casolo, Simone; Castiglioni, Ettore; Longhi, Giovanna; Martinazzo, Rocco; Panigati, Monica; Pappini, Marco; et al.
<x xml:space="preserve">Abstract</x> When new topologically appealing molecules are formed, fantasy‐assisted cogitation tries to associate their shapes to objects of everyday life: knots, cylinders, pretzels, baskets, ladders, etc. Chirality adds a touch of intelligence to these molecules, which gain the ability to recognize enantiomorphic species. In their Communication on page 15298 ff., F. Sannicolò et al. describe some inherently chiral elliptical and triangular oligothiophene macrocycles which they associate with the pictograms of some more or less mysterious crop circles. Photograph courtesy of Mr. Steve Alexander, www.temporarytemples.co.uk.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>